From the INVICTUS Trial to Current Considerations: It’s Not Time to Retire Vitamin K Inhibitors Yet! - Akshyaya Pradhan; Somya Mahalawat; Marco Alfonso Perrone (Pharmaceuticals)
Atrial fibrillation (AF) is a common arrhythmia in clinical practice, and oral anticoagulation is the cornerstone of stroke prevention in AF. Direct oral anticoagulants (DOAC) significantly reduce the incidence of intracerebral hemorrhage with preserved efficacy for preventing stroke compared to vitamin K antagonists (VKA). However, the pivotal randomized controlled trials (RCTs) of DOAC excluded patients with valvular heart disease, especially mitral stenosis, which remains an exclusion criterion for DOAC use. The INVICTUS study was a large multicenter global RCT aimed at evaluating the role of DOAC compared to VKA in stroke prevention among patients with rheumatic valvular AF. In this study, rivaroxaban failed to prove superiority over VKA in preventing the composite primary efficacy endpoints of stroke, systemic embolism, myocardial infarction, and death. Unfortunately, the bleeding rates were not lower with rivaroxaban either. The death and drug discontinuation rates were higher in the DOAC arm. Close to the heels of the dismal results of INVICTUS, an apixaban trial in prosthetic heart valves, PROACT-Xa, was also prematurely terminated due to futility. Hence, for AF complicating moderate-to-severe mitral stenosis or prosthetic valve VKA remains the standard of care. However, DOAC can be used in patients with surgical bioprosthetic valve implantation, TAVR, and other native valve diseases with AF, except for moderate-to-severe mitral stenosis. Factor XI inhibitors represent a breakthrough in anticoagulation as they aim to dissociate thrombosis from hemostasis, thereby indicating a potential to cut down bleeding further. Multiple agents (monoclonal antibodies—e.g., osocimab, anti-sense oligonucleotides—e.g., fesomersen, and small molecule inhibitors—e.g., milvexian) have garnered positive data from phase II studies, and many have entered the phase III studies in AF/Venous thromboembolism. Future studies on conventional DOAC and new-generation DOAC will shed further light on whether DOAC can dethrone VKA in valvular heart disease.